Population dynamics of Typhlodromalus limonicus from Colombia, an introduced predator of the exotic cassava green mite in West Africa - Rogg, H.W.; Yaninek, John S. (1990)
The introduction of Typhlodromalus limonicus (Garman & McGregor) sensu lato is a major component of an on-going biological control campaign against the exotic cassava pest Mononychellus tanajoa (Bondar) in Africa. However, long-term establishment of this exotic phytoseiid predator has not yet been achieved. The Colombian biotype of 33 limonicus was evaluated as a biological control agent in Nigeria and Bénin by assessing its population response to selected abiotic and biotic factors. In field experiments, 73 limonicus temporarily survived forca. 19 generations during wet and dry seasons. 73 limonicus population densities were negatively correlated with that of M. tanajoa suggesting its prédation potential on M. tanajoa. The spider mite populations were positively while the predatory mite populations were negatively affected by the low (< 50%) relative humidity during the dry season. Competition with endemic phytoseiid species on cassava was not evident. 73 limonicus was present on top leaves with M. tanajoa, whereas indigenous predators were more frequent on bottom leaves. Alternate prey may play a role in sustaining 73 limonicus populations during times of prey scarcity. Biotypes of a potential biological control agent for M. tanajoa should be selected to improve the chances of a successful establishment in Africa.